Optimalisasi Pencampuran Batubara Untuk Memenuhi Kriteria Permintaan Konsumen Dengan Menggunakan Metode Simplek dan Evaluasi Biaya Pada Proses Blending Batubara Di Lokasi CV. Tahiti Coal, Talawi, Sawahlunto, Sumatera Barat - Sonia Lestari; Rijal Abdullah (Journals Mining Engineering : Bina Tambang, 2018)
The quality of coal is influenced by the geological condition of a mining site, including high quality (higt quality), medium quality, and low quality. The amount of coal with calorific value ranges from 7600 kcal / kg to 7800 kcal / kg that has not been marketed accumulate in stockpile CV. Tahiti Coal. The high quality of coal in the CV. Tahiti Coal then not in accordance with the contract specifications with consumers. One of them with PT PLN (PERSERO) Sector Ombilin which require coal calorie 6300 kkal / kg. Therefore it is necessary for action to utilize high quality coal so as not to accumulate in CV stockpile. Tahiti Coal by mixing high quality coal with low quality coal.The simplex method is one of the mathematical models that can be used in solving the problem of allocation of finite sources optimally (maximum profit or minimum cost) of three or more variables.The results showed that the increase of calorific value from 6,283,08 Cal / gr, Ash 13,91%, sulfur 0,83% company result compared to comparison of method of calorific value value 6,328 Cal / gr, Ash 12,06%, sulfur 0.61% can be profitable for companies with a predetermined calorie value of 6,300 Cal / gr, Ash 13%, 0.8% sulfur. With the calculation of simplex method of the company can ease of work in the field. And calculation of coal blending cost for 1 month Rp. Total biaya blending Rp. 571.202.000Keywords: Blending, Coal, Calories, Simplek Method, Blending Cost